2021
DOI: 10.1177/0735633121992479
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors That Influence Computational Thinking Skills in Elementary Students’ Collaborative Robotics

Abstract: Recently educational robotics has expanded into curriculum beyond traditional STEM fields, and which can also be used to foster computational thinking (CT) skills. Prior research has shown numerous interdisciplinary benefits related to CT, however, these influential factors have often been investigated with relatively few variables. This study investigated factors that may lead to 4th and 5th grade elementary school students’ development of computational thinking skills in collaborative robotics activities by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…The robotic activities constitute the second largest percentage (41%) in developing CT in education. There were only 2 studies conducted in ASEAN countries (Sun et al, 2021a(Sun et al, , 2021bYi Wu & Yu Sheng, 2021) and 12 researches conducted in non-ASEAN countries (Critten et al, 2021;Fanchamps et al, 2019;Garcia Angarita et al, 2017;Ioannou & Makridou, 2018;Jaipal-Jamani & Angeli, 2017;Menolli & Neto, 2021;Merino-Armero et al, 2021;Ozmutlu et al, 2021;Piedade et al, 2020;Relkin et al, 2021;Silva et al, 2021;Stewart et al, 2021). This comprehensive research reveals how non-ASEAN countries employed robotic operations to produce CT skills better effectively.…”
Section: Robotic Activitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The robotic activities constitute the second largest percentage (41%) in developing CT in education. There were only 2 studies conducted in ASEAN countries (Sun et al, 2021a(Sun et al, , 2021bYi Wu & Yu Sheng, 2021) and 12 researches conducted in non-ASEAN countries (Critten et al, 2021;Fanchamps et al, 2019;Garcia Angarita et al, 2017;Ioannou & Makridou, 2018;Jaipal-Jamani & Angeli, 2017;Menolli & Neto, 2021;Merino-Armero et al, 2021;Ozmutlu et al, 2021;Piedade et al, 2020;Relkin et al, 2021;Silva et al, 2021;Stewart et al, 2021). This comprehensive research reveals how non-ASEAN countries employed robotic operations to produce CT skills better effectively.…”
Section: Robotic Activitiesmentioning
confidence: 94%
“…This comprehensive research reveals how non-ASEAN countries employed robotic operations to produce CT skills better effectively. Meanwhile, CT skills in collaborative robotics activities (Stewart et al, 2021), robotics activities in education (Ioannou & Makridou, 2018;Menolli & Neto, 2021;Silva et al, 2021), LEGO® WeDo robotics kits (Fanchamps et al, 2019;Jaipal-Jamani & Angeli, 2017), intensive coding course (Critten et al, 2021;Ozmutlu et al, 2021;Piedade et al, 2020), robotics club and course (Garcia Angarita et al, 2017;Yi Wu & Yu Sheng, 2021), BCTt and TechCheck (Relkin et al, 2021) and school extracurricular robotics activities (Merino-Armero et al, 2021) were used as effective tools in enhancing CT abilities. Unplugged programming exercises (Sun et al, 2021a(Sun et al, , 2021b and physical robot courses (Yi Wu & Yu Sheng, 2021) have also been shown to assist and improve CT skills in two ASEAN countries.…”
Section: Robotic Activitiesmentioning
confidence: 99%
“…Eight studies examined the role of partnership in collaborative CT learning, which refers to the pairing of students based on learning styles (Pürbudak & Usta, 2021; Zhong & Wang, 2021), learning preferences (Stewart et al, 2021), age (Saxena et al, 2020), and gender (Cheng et al, 2013; Taylor & Baek, 2019; Zhong et al, 2016). There were contradictory findings regarding the effects of learning style in collaborative learning.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the results indicated no statistically significant difference among different pairs of learning styles in CT learning achievements (Zhong & Wang, 2021). Regarding learning preference, learning preference was found to have a significant direct relationship with perceived competence but not with learning outcomes (Stewart et al, 2021). Another empirical study conducted with mixed‐age groups in a kindergarten showed that K1 children cannot learn well when paired with K2 and K3 students.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, behavioral engagement has been defined as the correspondence between the child’s behavior and the situation’s demands ( Ponitz et al, 2009 ), and has been positively associated with academic achievement ( Lei et al, 2018 ). Recent evidence from educational robotics (ER) has shown learning motivation to be associated with performance in problem-solving and computational thinking during primary school ( Stewart et al, 2021 ). Thus, understanding children’s engagement during ER tasks is highly relevant to their later performance.…”
Section: Introductionmentioning
confidence: 99%